OH SEHUN'S BRAND AMBASSADOR REPRESENTATION FOR WHITELAB PRODUCTS ON INSTAGRAM - Armilia, Elfira; Aesthetika , Nur Maghfirah (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the meaning of visual signs in Whitelab's Instagram content featuring Oh Sehun as a brand ambassador, using Charles Sanders Peirce's semiotic approach. This study examines how visual elements such as photos, text, and colors displayed in Instagram posts can build brand image and influence audience perception of Whitelab products. Method: Using triadic semiotics theory involving representamen, object, and interpretant, this study identifies how visual signs interact to form meanings understood by the audience. Results: Data was collected through documentation of Whitelab's official Instagram posts featuring Oh Sehun and analyzed qualitatively to understand how brand messages are constructed and received by the audience. Novelty: The results of this study show that the representation of visual elements such as poses, colors, and text in promotions serves to reinforce Whitelab's image as a modern and scientific premium skincare brand, as well as strengthen emotional connections with the audience, especially K-pop fans.